2015
DOI: 10.1002/lary.25125
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of effective continuous positive airway pressure in patients with obstructive sleep apnea/hypopnea syndrome

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 16 publications
0
17
0
6
Order By: Relevance
“…have found that the obstruction at tongue base level may predict the level of optimal CPAP pressure required for the patient. 11 In our study, we found that a CPAP pressure of 15 cm H 2 O was effective for treating tongue base collapse and increasing airway volume within the retrolingual region (Figure 2, Video 2).…”
Section: Discussionmentioning
confidence: 58%
“…have found that the obstruction at tongue base level may predict the level of optimal CPAP pressure required for the patient. 11 In our study, we found that a CPAP pressure of 15 cm H 2 O was effective for treating tongue base collapse and increasing airway volume within the retrolingual region (Figure 2, Video 2).…”
Section: Discussionmentioning
confidence: 58%
“…There were 4,436 patients in the development phases and 3,489 patients in the validation phases for the combined studies included in this review. The earliest published study was by Miljeteig and Hoffstein [ 38 ] in 1993 and the most recent study was published in 2015 [ 56 ]. Table 1 presents the study quality assessment for the individual studies.…”
Section: Resultsmentioning
confidence: 99%
“…Additional Variables . The updated Friedman Tongue Position was a variable in the study by Lai et al [ 56 ]. Smoking in pack years was a variable in the formulas derived by Schiza et al [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research evaluating the possible influential factors in CPAP titration, aimed at lowering economic costs and significantly increasing the tolerance of CPAP therapy, have produced varying results [10,13,14]. A systematic review by Camacho et al [10] showed that BMI and ODI weighed most heavily in the equation that predicted the CPAP titration level.…”
Section: Discussionmentioning
confidence: 99%